Question and Answers Forum

All Questions      Topic List

Arithmetic Questions

Previous in All Question      Next in All Question      

Previous in Arithmetic      Next in Arithmetic      

Question Number 183989 by HeferH last updated on 01/Jan/23

(((√x) + (√(x − 4a)))/( (√x) − (√(x − 4a)))) = a ≠ 0   find “x” in terms of “a”.

x+x4axx4a=a0findxintermsofa.

Commented by Frix last updated on 01/Jan/23

I get x=(a+1)^2

Igetx=(a+1)2

Answered by Rasheed.Sindhi last updated on 01/Jan/23

(((√x) + (√(x − 4a)))/( (√x) − (√(x − 4a)))) = a ≠ 0   find “x” in terms of “a”.   (((√x) +(√(x−4a)) )/( (√x) −(√(x−4a)) ))+1=a+1  ((2(√x))/( (√x) −(√(x−4a)) ))=a+1  2(√x) =a(√x) −a(√(x−4a)) +(√x) −(√(x−4a))   a(√x) −(√x) =a(√(x−4a)) +(√(x−4a))   (√x) (a−1)=(√(x−4a)) (a+1)  (((√(x−4a)) )/( (√x)))=((a−1)/(a+1))  ((x−4a)/x)=(((a−1)/(a+1)))^2   1−((4a)/x)=((a^2 −2a+1)/(a^2 +2a+1))  −((4a)/x)=((a^2 −2a+1)/(a^2 +2a+1))−1=((−4a)/((a+1)^2 ))  (1/x)=(1/((a+1)^2 ))      [∵ a≠0]  x=(a+1)^2

x+x4axx4a=a0findxintermsofa.x+x4axx4a+1=a+12xxx4a=a+12x=axax4a+xx4aaxx=ax4a+x4ax(a1)=x4a(a+1)x4ax=a1a+1x4ax=(a1a+1)214ax=a22a+1a2+2a+14ax=a22a+1a2+2a+11=4a(a+1)21x=1(a+1)2[a0]x=(a+1)2

Answered by a.lgnaoui last updated on 01/Jan/23

((((√x) +(√(x−4a)) )^2 )/(4a))=a  2x−4a+2(√(x(x−4a))) =4a^2   (√(x(x−4a))) =2a^2 +2a−x  x(x−4a)=4a^4 +4a^2 +x^2 +8a^3 −4a^2 x−4ax  x^2 −4ax=x^2 −4ax(a+1)+4a^2 (a^2 +2a+1)  0=4a^2 (a+1)^2 −4a^2 x            x=(a+1)^2

(x+x4a)24a=a2x4a+2x(x4a)=4a2x(x4a)=2a2+2axx(x4a)=4a4+4a2+x2+8a34a2x4axx24ax=x24ax(a+1)+4a2(a2+2a+1)0=4a2(a+1)24a2xx=(a+1)2

Answered by manolex last updated on 01/Jan/23

m=(√x)  n=(√(x−4a))  ((m+n)/(m−n))=a  m^2 =x  n^2 =x−4a  m^2 −n^2 =4a  (m+n)(m−n)=4a  ((m+n)/(m−n))=a        m≠n  (m+n)^2 =4a^2   m+n=2a    ∨    m+n=−2a  m−n=2              m−n=−2  2m=2a+2          2m=−2(a+1)  m=a+1                   m=−(a+1)  (√x)=a+1                 (√x)=−(a+1)  x=(a+1)^2                 x=(a+1)^2   solucion    x=(a+1)^2   comprobacion  ((a+1+(√((a+1)^2 −4a)))/(a+1−(√((a+1)^2 −4a))))=((a+1+(a−1))/(a+1−(a−1)))=((2a)/2)=a   correcto

m=xn=x4am+nmn=am2=xn2=x4am2n2=4a(m+n)(mn)=4am+nmn=amn(m+n)2=4a2m+n=2am+n=2amn=2mn=22m=2a+22m=2(a+1)m=a+1m=(a+1)x=a+1x=(a+1)x=(a+1)2x=(a+1)2solucionx=(a+1)2comprobaciona+1+(a+1)24aa+1(a+1)24a=a+1+(a1)a+1(a1)=2a2=acorrecto

Answered by Rasheed.Sindhi last updated on 01/Jan/23

(((√x) + (√(x − 4a)))/( (√x) − (√(x − 4a)))) = a ≠ 0   find “x” in terms of “a”.   (√x) +(√(x−4a)) =a(√x) −a(√(x−4a))   a(√x) −(√x) =(√(x−4a)) +a(√(x−4a))  (√x) (a−1)=(√(x−4a)) (a+1)  (((√(x−4a)) )/( (√x)))=((a−1)/(a+1))  ((x−4a)/x)=((a^2 −2a+1)/(a^2 +2a+1))  ((x−4a)/x)−1=((a^2 −2a+1)/(a^2 +2a+1))−1  ((−4a)/x)=((−4a)/((a+1)^2 ))  (1/x)=(1/((a+1)^2 ))     [∵a≠0]  x=(a+1)^2

x+x4axx4a=a0findxintermsofa.x+x4a=axax4aaxx=x4a+ax4ax(a1)=x4a(a+1)x4ax=a1a+1x4ax=a22a+1a2+2a+1x4ax1=a22a+1a2+2a+114ax=4a(a+1)21x=1(a+1)2[a0]x=(a+1)2

Terms of Service

Privacy Policy

Contact: info@tinkutara.com